Assessment of Thermal Conditions by Slow Solidification in Al Alloys and the Facility - P. Mikolajczak (Archives of Foundry Engineering)
Mold filling and casting solidification are determined by gravity driven natural convection. Also forced convection induced by rotating magnetic field influences castings microstructure. The investigations of flow effect on the aluminum casting alloys and silicon rich alloys were mainly conducted on simple cylindrical specimens and focused on the microstructure, composition and strength of electromagnetic field. Unfortunately, the temperature field in the specimens and facility were mainly omitted or not enough discussed. In the current study thermal conditions in a special facility for flow effect investigation were studied, in experimental and numerical manner, concerning Al-Si-Mg alloys with various compositions and different solid fraction curves. Solidification simulation has proven slow cooling and uniform temperature on the cross-section of the specimen and crucible, nearly uniform solidification time throughout the whole specimen, wide mushy zone and proper construction of the facility protecting electric coils. Temperature gradient and cooling rate, for alloys where almost all solid fraction and latent heat released close to solidus, were significantly higher at the solidus temperature than by liquidus, whilst in alloys where latent heat released evenly and closer to liquidus, were smoothly changing across sample and from liquidus to solidus temperature. Numerically simulated microstructure parameters like e.g. SDAS, grain size and fraction of primary phase in α-Al first alloy presented values similar and smoothly changing across specimen. It was proposed to calculate secondary dendrite arm spacing SDAS based on the specified time period, that could be responsible for melting some arms or creating new arms by dendrites, and next careful SDAS measurement across specimen was recommended. Tested facility and experimental procedure, developed for studying flow effect on the Al alloys microstructure, was proven to be very resistant to interference.